2007
DOI: 10.1186/ar2328
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of dendritic cells and macrophages during T cell-mediated synovial inflammation

Abstract: Adoptive transfer of adjuvant-induced arthritis was used in this study to examine local macrophages and dendritic cells (DCs) during T cell-mediated synovial inflammation. We studied the influx of CD11b + CD11c + putative myeloid DCs and other nonlymphoid CD45 + cells into synovium-rich tissues (SRTs) of the affected hind paws in response to a pulse of autoreactive thoracic duct cells. Cells were prepared from the SRTs using a collagenase perfusion-digestion technique, thus allowing enumeration and phenotypic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 43 publications
(77 reference statements)
5
23
0
Order By: Relevance
“…Previous studies published from this laboratory have been conducted using rats fed a standard rat chow diet 17 , 18 , 20 . An initial comparison was made, therefore, between ATA induced in vit D − mature offspring from dams fed the vit D − diet and in age‐matched rats fed standard chow.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies published from this laboratory have been conducted using rats fed a standard rat chow diet 17 , 18 , 20 . An initial comparison was made, therefore, between ATA induced in vit D − mature offspring from dams fed the vit D − diet and in age‐matched rats fed standard chow.…”
Section: Resultsmentioning
confidence: 99%
“…Panayi et al 19 have suggested a similar mechanism of local recruitment and re‐stimulation of activated T cells in rheumatoid synovium. During the evolution of ATA, host‐derived MHC II hi mononuclear cells of myelo‐monocytic lineage accumulate in SRTs and many of these cells express CD11c and have the phenotypic characteristics of dendritic cells (DCs) in varying states of maturity 20 . Only a minority (∼20%) expressed the macrophage marker CD163.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Flow cytometric analysis extending beyond assessment of CD11b or Gr-1 expression has only been reported in rats (Moghaddami et al, 2005a; Moghaddami et al, 2007; Moghaddami et al, 2005b) or synovial fluid of knee joints (Bruhns et al, 2003). None of these studies included techniques that determined the origin of synovial macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Cytospin smears prepared from flow cytometrically sorted cells were fixed and stained as described [18]. …”
Section: Methodsmentioning
confidence: 99%